The statistical study between the heights calculated by GNSS and the values of the vertical network within the regulatory planning area - Latakia city - هتره أمجد; محسن أحمد; وائل ديوب (Latakia University Journal -Engineering Sciences Series, 2023)
The research aims to accomplish a theoretical and practical study related to high-rise works within two geodetic height networks. The first is the geodetic height network that was established for the purpose of developing the master plan of Latakia city, and the second is the global height network within the geodetic reference EGM2008, in order to find a constant numerical relationship between them. It can be said that the project of connecting heights calculated by GNSS and the height network within the survey project of Latakia city is an important and useful project, as it improves the accuracy of geographic data for the area and enhances the ability to analyze data and make informed decisions. The research results showed that the vast majority of reference height points have been lost due to various natural and artificial factors. The relationship between the heights calculated by any of the GNSS measurement methods was determined, which can be done at any time and under any circumstances by adding the value of 0.284 m, obtained with an accuracy of 0.038 m. It was found that a fourth-degree vertical path can be created with a distance between two consecutive points of approximately 600 m..